Medication effectiveness may not be the major reason for accepting cardiovascular preventive medication: A population-based survey - Harmsen, Charlotte Gry (BioMed Central, 2012)
BACKGROUND: Shared decision-making and patients’ choice of interventions are areas of increasing importance, not least seen in the light of the fact that chronic conditions are increasing, interventions considered important for public health, and still non-acceptance of especially risk-reducing treatments of cardiovascular diseases (CVD) is prevalent. A better understanding of patients’ medication-taking behavior is needed and may be reached by studying the reasons why people accept or decline medication recommendations. The aim of this paper was to identify factors that may influence people’s decisions and reasoning for accepting or declining a cardiovascular preventive medication offer. METHODS: From a random sample of 4,000 people aged 40–59 years in a Danish population, 1,169 participants were asked to imagine being at increased risk of cardiovascular disease and being offered a preventive medication. After receiving ‘complete’ information about effectiveness of the medication they were asked whether they would accept medication. Finally, they were asked about reasons for the decision. RESULTS: A total of 725 (67%) of 1,082 participants accepted the medication offer. Even quite large effects of medication (up to 8 percentage points absolute risk reduction) had a smaller impact on acceptance to medication than personal experience with cardiovascular disease. Furthermore, increasing age of the participant and living with a partner were significantly associated with acceptance. Some 45% of the respondents accepting justified their choice as being for health reasons, and they were more likely to be women, live alone, have higher income and higher education levels. Among those who did not accept the medication offer, 56% indicated that they would rather prefer to change lifestyle. CONCLUSIONS: Medication effectiveness seems to have a moderate influence on people’s decisions to accept preventive medication, while factors such as personal experience with cardiovascular disease may have an equally strong or stronger influence, indicating that practitioners could do well to carefully identify the reasons for their patients’ treatment decisions.